The Prevalence of HCV Infection Among Healthcare Workers in Dhaka City - Ghosh, Dilip Kumar; Rana, Syed Alamgir Safwath; Ghosh, Chanchal Kumar; Mahmuduzaman, Md.; Rahman, Md. Mustafizur; Rahma, Anisur (Journal of Shaheed Suhrawardy Medical College, 2012)
J Shaheed Suhrawardy Med Coll ?Volume 2 Number 2 December 2010 ? Page 12-17 DOI: http://dx.doi.org/10.3329/jssmc.v2i2.12047